2020
DOI: 10.13189/cea.2020.080408
|View full text |Cite
|
Sign up to set email alerts
|

Transport Sediment Analysis Using Bed-load: Case Study Bilibili Reservoir

Abstract: This study conducted to analyze transport sediment using bed-load in the Bilibili reservoir case, South Sulawesi, Indonesia. The laboratory test has done to determine the basic characteristics of samples consisting of sediment concentration tests and specific gravity tests. Furthermore, the data analysis using Van Rijn formulation to calculate bed sediment discharge (Qb) and flow rate (Q), and analysis result found the relationship between bed sediment discharge and flow rate expressed in equation y = 12.314x1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
0
3
0
2
Order By: Relevance
“…Intensitas curah hujan adalah ketinggian curah hujan yang terjadi pada kurun waktu dimana air tersebut terkonsentrasi. Intensitas curah hujan dinotasikan dengan huruf I dengan satuan mm/jam [3]. Perlunya menghitung curah hujan rata-rata wilayah adalah untuk penyusunan suatu rancangan pemanfaatan air dan rancangan pengendalian banjir.…”
Section: Pendahuluanunclassified
See 1 more Smart Citation
“…Intensitas curah hujan adalah ketinggian curah hujan yang terjadi pada kurun waktu dimana air tersebut terkonsentrasi. Intensitas curah hujan dinotasikan dengan huruf I dengan satuan mm/jam [3]. Perlunya menghitung curah hujan rata-rata wilayah adalah untuk penyusunan suatu rancangan pemanfaatan air dan rancangan pengendalian banjir.…”
Section: Pendahuluanunclassified
“…Hidrograf satuan sintetik ini dikembangkan oleh Sri Harto yang diturunkan berdasarkan teori hidrograf satuan sintetik yang dikemukakan oleh Sherman. Hidrograf satuan sintetik Gama-I merupakan persamaan empiris yang diturunkan dengan mendasarkan pada parameter-parameter DAS terhadap bentuk dan besaran hidrograf satuan parameter-parameter DAS tersebut yaitu faktor sumber (SF), frekuensi sumber (SN), factor lebar (WF), luas relatif (RUA), faktor simetris (SIM) dan jumlah pertemuan sungai [3]. Penelitian yang pernah dilakukan oleh Hinari (2014) Analisis Debit Banjir Rancangan untuk Perancanaan Bendung Randangan.…”
Section: Pendahuluanunclassified
“…Bili-Bili Reservoir is a multi-purpose reservoir and the largest in South Sulawesi, located in Gowa Regency, South Sulawesi, Indonesia. One of the reservoir purposes is to provide clean water to Makassar City, Gowa, Takalar, and Maros Regency (Lukman et al 2020a(Lukman et al , 2020b. In 2004, a landslide occurred in the Bawakaraeng Mountain, carrying around 200 million m 3 of landslide material, resulting in an increase of turbidity in the reservoir ranging from 29,000 to 52,000 Nephelometric Turbidity Unit (NTU) and exceeding the permissible threshold (6,000 NTU) (Yusuf et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the peak discharge was obtained at 1125.14 m/second which occurred on December 21, 2017. And finally, the peak discharge was obtained at 645.56 m³/second which occurred on February 15, 2018[6],[7].Based on the inflow discharge data of the Bili-bili Reservoir in 2014 -2018, using the Mononobe Method, with an effective rain duration of 4 hours for t=1, the rainfall resulted in a peak discharge that occurred on that date of 30.439 mm/day. in the Bilibili Reservoir in 2015, the rainfall which resulted in the peak discharge on the above date was 80.1 mm/day.…”
mentioning
confidence: 99%
“…It was found that the rainfall that produced the peak discharge on that date was 56.4 mm/day. More details as in the following table[5]-[7].…”
mentioning
confidence: 99%